The Frisco kid [videorecording (Blu-Ray)] - Wilder, Gene, 1933-2016; Ford, Harrison, 1942-; Neufield, Mace; Aldrich, Robert, 1918-1983 (Warner Bros. Entertainment Inc., 2022)
A sweetly innocent Polish rabbi travels through 1850s America toward his new congregation and wife in San Francisco. Along the way, he forms an uneasy alliance with an inept bank robber and the two cut a pratfall-filled path across the wild west.